Drying of antioxidant composite materials based on table beet - Petrovaa, Zhanna; Snezhkіna, Yuriy; Pazyukb, Vadym; Samoilenkoa, Kateryna (Lviv Polytechnic National University, 2015)
Reduction in the cost of energy in the food industry is an important challenge today due to increased prices. Drying process of plant material refers to the complex energy-intensive processes. Solution of this problem is the development of drying methods that would reduce energy consumption by the process. In the drying of plant material, another major factor is the quality indicators of the finished product, which depend mainly on the drying technology. Therefore, in the Institute of Technical Thermal Physics, energy-efficient drying modes of plant material that made it possible to reduce energy consumption at the drying process and to preserve the biologically active substances of the feedstock were developed. Research is devoted to developing energy-efficient drying modes of antioxidant materials based on table beet that provide betanin saving by 95 % and reducing energy consumption by 49 %. Today in Ukraine, there are not enough companies processing plant materials in powder, thus preserving the quality of the feedstock. Зниження затрат енергоносіїв у харчовій промисловості є актуальним завданням сьогодення у зв’язку з підвищенням цін на них. Процес сушіння рослинної сировини належить до складних енергоємних процесів. Одним із шляхів вирішення цієї проблеми є розробка таких способів сушіння, які б дали змогу знизити енергозатрати на процес. Під час сушіння рослинної сировини ще одним важливим фактором є якісні показники готового продукту, які залежать головно від технології сушіння. Тому в Інституті технічної теплофізики розроблено енергоефективні режими сушіння рослинної сировини, що дали можливість зменшити енерговитрати на процес сушіння та максимально зберегти біологічно активні речовини вихідної сировини. Досліджено розроблення енергоефективних режимів сушіння антиоксидантної сировини на основі буряку, які забезпечують збереження бетаніну на 95% і зменшення витрат енергії на 49 %. Сьогодні в Україні недостатньо виробництва з переробки рослинної сировини в порошки, що дає змогу зберегти якість вихідної сировини.
Сушіння антиоксидантної композиційної сировини на основі столового буряку
Keywords: antioxidants; beet; betanin; drying; saving; energy costs; антиоксиданти; буряк; бетанін; сушіння; збереження; витрати енергії